Pengaruh Flashcard Ekspresi Terhadap Perkembangan Kognitif Anak Usia Prasekolah - Saputri Indah Lestari; Ari Damayanti Wahyuningrum; Ari Dwi Sulaksono (STIKES Widyagama Husada, 2026)
Abstract The cognitive development of The cognitive development of preschool children is crucial, as this period is often referred to as the